Secure distributed power trading protocol for networked microgrids based on blockchain and elliptic curve cryptography. Issue 2 (18th October 2022) - Fkaier, Soumoud; Khalgui, Mohamed; Frey, Georg; Li, Zhiwu; Yu, Jiaxin
Abstract: The definition of an electricity trading protocol among microgrids is not an easy task to perform due to the grid's increasing requirements. In fact, a trading process must provide security and especially privacy of the buyer and seller identities as well as prices. Also, guaranteeing a financial profit to trading parties is of great importnace. Moreover, matching the full distributed paradigm is required since it will be executed in a distributed system. All these constraints must be satisfied with consideration to the computational costs especially data storage. In this paper, an electricity trading protocol is introduced to ensure: (1) the security and privacy of buyers, sellers, and sales information, (2) the trading process distribution, and (3) the minimisation of the stored data. The protocol builds upon the blockchain technology and the Elliptic Curve Cryptography. To achieve the protocol goals, a new architecture based on a concept of membership of microgrids to families and groups of families is defined. The proposed protocol is implemented using Java programming langauge. An honest‐but‐curious‐adversary security model is applied to a formal case study to prove security of the protocol. Abstract : In this paper, an electricity trading protocol is introduced to ensure: (1) the security and privacy of buyers, sellers, and sale information, (2) the trading process distribution, and (3) the minimization of the data storage requirements.